Analisis Literatur Etika Administrasi dan Dampaknya pada Pengambilan Keputusan Birokrasi di Kabupaten Pulang Pisau - Dicky Setiawan Hidayat; Intan Kumala Sari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the interplay between administrative ethics and bureaucratic decision-making within the governance landscape of Pulang Pisau Regency through a structured literature analysis. Anchored in the theoretical frameworks of Administrative Ethics Theory, Bureaucratic Decision-Making Theory, and Good Governance, this research synthesizes classical and contemporary scholarly works to identify the determinants, challenges, and institutional dynamics that influence ethical decision processes in local bureaucracy. The method employs a qualitative narrative literature review, involving systematic identification, screening, quality assessment, and thematic extraction of relevant academic sources published in the last two decades. Findings indicate that ethical norms, integrity, organizational culture, leadership morality, and institutional control mechanisms significantly shape the rationality, consistency, and legitimacy of bureaucratic decisions. Furthermore, the literature reveals that external pressures, conflict of interest, inadequate regulatory enforcement, and limited administrative capacity remain persistent barriers to the implementation of ethical governance in regional administrations. The study also highlights the essential role of participatory governance, digitalization, and internal accountability frameworks in strengthening ethical consistency across bureaucratic processes. These insights position administrative ethics as a crucial foundation for promoting transparency, fairness, and public trust in local government institutions. The paper concludes that strengthening administrative ethics requires integrated institutional reforms, long-term commitment, and the internalization of ethical values at both organizational and individual levels. The implications of this research extend to policy formulation, bureaucratic capacity-building, and future empirical studies on ethical governance in decentralized contexts.